2012
DOI: 10.1007/s12272-012-1012-z
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic effects of Ganoderma lucidum polysaccharides in type 2 diabetic mice

Abstract: Our aims were to investigate the hypoglycemic effects and mechanisms of action of Ganoderma lucidum polysaccharides (GLPs) administered for 7 days in type 2 diabetic mice. The mice were randomly divided into four groups (8 mice/group): normal control group, diabetic control group, low-dose GLP-treated diabetic group (50 mg/kg/d), and high-dose GLP-treated diabetic group (100 mg/kg/d). Diabetes was induced by streptozotocin injection and high-fat dietary feeding. At the end of the study, fasting serum glucose, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 45 publications
2
58
1
1
Order By: Relevance
“…Moreover, the expression levels of G6PC1, a key regulatory enzyme in gluconeogenesis for catalyzing the final reaction step in hepatic glucose production, and PEPCK, for catalyzing the conversion of oxaloacetate (OAA) to phosphoenolpyruvate (PEP) was down-regulated following the RS administration. Thus, the current investigation might indicate that the decrease in fasting blood glucose level might be also partially associated with decreased mRNA expression levels of PEPCK and G6PC1, which was in line with other study using Ganoderma lucidum polysaccharides for the diabetic intervention [14].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the expression levels of G6PC1, a key regulatory enzyme in gluconeogenesis for catalyzing the final reaction step in hepatic glucose production, and PEPCK, for catalyzing the conversion of oxaloacetate (OAA) to phosphoenolpyruvate (PEP) was down-regulated following the RS administration. Thus, the current investigation might indicate that the decrease in fasting blood glucose level might be also partially associated with decreased mRNA expression levels of PEPCK and G6PC1, which was in line with other study using Ganoderma lucidum polysaccharides for the diabetic intervention [14].…”
Section: Discussionsupporting
confidence: 92%
“…Due to their significant medicinal importance, mushrooms of the Ganoderma species have gained noticeable interest from biomedical researchers. A number of studies have revealed the medicinal values of Ganoderma mushrooms against various life-threatening diseases and health complications like cancer, immunodeficiency, cardiovascular complications, diabetes, hepatic disease, neurodegeneration, and infectious disease (Hajjaj et al, 2005;Paterson, 2006;Ma et al, 2011;Chu et al, 2012;Tie et al, 2012;Xiao et al, 2012;Boh, 2013;Wang et al, 2013;Wu et al, 2013;Yue et al, 2013). There are numerous variations in the size, shape, and color of Ganoderma mushrooms, and they differ in biological properties as well.…”
Section: Introductionmentioning
confidence: 99%
“…The antihyperglycemic effects of several plant extracts and herbal prescriptions, which are used as antidiabetic formulations, have been confirmed Sun et al, 2015;Wang et al, 2012;Xiao et al, 2012;Xie et al, 2011;Zhang et al, 2015). Polygonati Rhizoma, first P. kingianum is widely reported and used as adjuvant therapy drug of diabetes in favor of its blood glucose level lowing effects ( Chen et al, 2001;Deng et al, 2012;Kato and Miura, 1994;Roh et al, 2008;).…”
Section: Introductionmentioning
confidence: 98%